A systematic review of pathophysiological and psychosocial measures in adaptive sports and their implications for coaching practice - Junyan Liu; Hongjun Yu; W. Catherine Cheung; Adam Bleakney; Yih-Kuen Jan (Heliyon)
Background: The pathophysiological and psychosocial factors influencing athletes with disabilities are crucial to their sports performance and well-being. This systematic review aims to provide evidence-based insights into how these factors should be adopted into coaching practice. Methods: The systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A comprehensive search of PubMed, Web of Science, SPORTDiscus, and Google Scholar was conducted, and studies were selected based on clear inclusion and exclusion criteria. Thirty-six studies met these criteria and were included in the thematic analysis. Results: In the pathophysiological domain, effective coaching requires adaptive training programs tailored to address the specific physical and physiological challenges of athletes with disabilities. These strategies include injury prevention, performance optimization, and management of muscle imbalance and altered musculoskeletal biomechanics. The psychosocial domain emphasizes the importance of emotional support, resilience-building, and social inclusion, with coaches playing a key role in helping athletes navigate challenges such as social stigma, emotional stress, and reduced self-confidence. Conclusion: This review underscores the necessity of a comprehensive coaching approach that integrates both pathophysiological and psychosocial considerations, enabling coaches to address the complex needs of athletes with disabilities. Synthesized findings provide actionable recommendations for individualized coaching strategies. These insights have significant implications for advancing coaching practices and promoting inclusivity in sports environments for all athletes.